Online Dialogue And Interaction Disruption. A Latin American Government’s Use Of Twitter Affordances To Dissolve Online Criticism - Davalos, Carlos (Universidad Autónoma de Nuevo León (UANL), 2020)
Few academic studies have focused on how Latin American governments operate online. Political communication studies focused on social media interactions have overwhelmingly dedicated efforts to understand how regular citizens interact and behave online. Through the analysis of hashtags and other online strategies that were used during Mexican President Enrique Peña Nieto’s (EPN) term to critique or manifest unconformity regarding part of the government’s performance, this study observes how members of a Latin American democratic regime weaponized a social media platform to dissipate criticism. More specifically, it proposes that the manipulation of social media affordances can debilitate essential democratic attributes like freedom of expression. Using a qualitative approach, consisting of observation, textual analysis, and online ethnography, findings show that some Mexican government’s manipulation of inconvenient Twitter conversations could impact or even disrupt potential offline crises. Another objective of the presented research is to set a baseline for future efforts focused on how Latin American democratic regimes behave and generate digital communication on social media platforms.